2021
DOI: 10.3390/ijerph182413389
|View full text |Cite
|
Sign up to set email alerts
|

Have You Heard That—“GOSSIP”? Gossip Spreads Rapidly and Influences Broadly

Abstract: This study examines the impact of negative workplace gossip (NWG) on employee political acts (PA) and the role of ego depletion (ED) as a mediator. We also examined the indirect impact of NWG on PA through ED controlled by emotional intelligence (EI). A three-wave time-lagged study (paper-pencil based) was performed with 277 employees from various private organisations in Islamabad, Pakistan. The current data were gathered in three phases to reduce common method bias. Study results indicate that NWG positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 85 publications
2
27
0
Order By: Relevance
“…The 􀅫indings shows that majority of the respondents belonged to those skilled persons who were agreed with private organizations taking an interest in conducting vocational training courses. Previous research also 􀅫inds similar 􀅫indings (Ullah et al, 2021;Moodie, 2002). The 􀅫indings of the study also observed that the majority of respondents were agreed that their institutes are providing skills according to international standards.…”
Section: Discussionsupporting
confidence: 67%
“…The 􀅫indings shows that majority of the respondents belonged to those skilled persons who were agreed with private organizations taking an interest in conducting vocational training courses. Previous research also 􀅫inds similar 􀅫indings (Ullah et al, 2021;Moodie, 2002). The 􀅫indings of the study also observed that the majority of respondents were agreed that their institutes are providing skills according to international standards.…”
Section: Discussionsupporting
confidence: 67%
“…As previously stated, this illustrates that, when serious wrongdoings occur frequently, it increases the likelihood that whistleblowers will own up to and disclose wrongdoings on their own [22,27,40]. When the wrongdoing is substantial, a whistleblower is more likely to take action [58]. In addition, a wrongdoing's seriousness is linked to the intensity of inescapable repercussions, and this influences people's ethical decision-making [30].…”
Section: Perceived Seriousness Of Wrongdoing and Whistleblowing Inten...mentioning
confidence: 66%
“…The whistleblower first evaluates the depth of the wrongdoing before whistleblowing. This activity is performed to judge the seriousness and course of action to be completed before it causes harm to the organization or employee [6,29,38,57,58]. With respect to perceived seriousness of wrongdoing, [36] states that an increase in the seriousness of wrongdoing will likely stimulate and impact a whistleblower's intent to come forward with their information.…”
Section: Perceived Seriousness Of Wrongdoing and Whistleblowing Inten...mentioning
confidence: 99%
“… 19 Pakistan is a collectivist culture, and people have strong bonds with one another. 20 In Pakistani culture, youngsters follow their elders and respect teachers, leaders, and managers. 21 On the basis of the above justification, this study will contribute more in the Pakistani context.…”
Section: Introductionmentioning
confidence: 99%